Assessment of knowledge and perceptions on leishmaniasis: An island-wide study in Sri Lanka - Rajika Dewasurendra; Hermali Silva; Nilakshi Samaranayake; Nuwani Manamperi; Nissanka de Silva; Panduka Karunanayake; Upul Senarath; Sanath Senanayake; Guofa Zhou; Nadira Karunaweera (Public Library of Science (PLoS), 2022)
Cutaneous leishmaniasis (CL) is a notifiable disease in Sri Lanka with increasing case numbers reported from every part of the country. In addition to disease treatment and vector control measures, knowledge and perceptions in a community are key contributors to a successful intervention program. An island-wide survey was carried out to assess the knowledge and perceptions regarding CL across the island, with 252 confirmed CL cases and 2,608 controls. Data was collected by trained personnel, using a pre-tested Case Reporting Form (CRF). Although the percentage who referred to CL by its correct name was low (1.4%), majority stated that it is a fly induced skin disease (79.1%). Knowledge on the symptoms, curability and the name of the vector was high in these communities, but specific knowledge on vector breeding places, biting times and preventive methods were poor. The patients were more knowledgeable when compared to the controls. Differences in the level of knowledge could be identified according to the level of education of the participants as well as across the different areas of the country. The main source of information was through the healthcare system, but the involvement of media in educating the communities on the disease was minimal. While this study population was unaccustomed to the use of repellants or sprays, the use of bed nets was high (77.7% of the participants) in this study population. Although misconceptions and incorrect practices are rare in Sri Lankan communities, promoting health education programs which may improve disease awareness and knowledge on vector and its control will further strengthen the control and prevention strategies. Author summary Cutaneous leishmaniasis (CL) is a disease which causes skin ulcers and spread by the sand fly. In recent years, the number of CL patients reported from all parts Sri Lanka increased notably, indicating that the spread of the disease should be controlled. The general publics' knowledge on the disease and its control methods, is very important to implement a successful control program. Thus, this study was conducted to assess the level of knowledge of the local community on CL, its vector and control methods. The required information was collected by interviewing CL patients as well as healthy persons. More than 50% of both groups gave correct answers to more general questions about the disease such as the disease name, symptoms and spread, indicating that the awareness of CL among the public is satisfactory. However, the study also indicated that the patients were more knowledgeable when compared to the healthy persons. Furthermore, it was evident that knowledge on more detailed information such as vector breeding places, vector biting times is poor in both groups and the healthcare system has been the primary source of information.